2011
DOI: 10.1007/s11517-011-0732-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and prediction of mRNA polyadenylation sites in human genes

Abstract: The accurate identification of potential poly(A) sites has contributed to all many studies with regard to alternative polyadenylation. The aim of this study was the development of a machine-learning methodology that will help to discriminate real polyadenylation signals from randomly occurring signals in genomic sequence. Since previous studies have revealed that RNA secondary structure in certain genes has significant impact, the authors tried to computationally pinpoint common structural patterns around the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…A number of studies have demonstrated that information from relatively short upstream and downstream sequences of the candidate poly(A) motifs can specify the true poly(A) motifs to a great extent (Ahmed et al , 2009; Akhtar et al , 2010; Chang et al , 2011; Cheng et al , 2006; Graber et al , 1999; Ji et al , 2010; Kalkatawi et al , 2012; Legendre and Gautheret, 2003; Liu et al , 2005; Salamov and Solovyev, 1997; Tabaska and Zhang, 1999). Statistical properties of the surrounding sequences were explored in different species, such as yeast (van Helden et al , 2000), fly (Retelska et al , 2006), Arabidopsis and rice (Ji et al , 2010) and human (Chang et al , 2011; Retelska et al , 2006; Tabaska and Zhang, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that information from relatively short upstream and downstream sequences of the candidate poly(A) motifs can specify the true poly(A) motifs to a great extent (Ahmed et al , 2009; Akhtar et al , 2010; Chang et al , 2011; Cheng et al , 2006; Graber et al , 1999; Ji et al , 2010; Kalkatawi et al , 2012; Legendre and Gautheret, 2003; Liu et al , 2005; Salamov and Solovyev, 1997; Tabaska and Zhang, 1999). Statistical properties of the surrounding sequences were explored in different species, such as yeast (van Helden et al , 2000), fly (Retelska et al , 2006), Arabidopsis and rice (Ji et al , 2010) and human (Chang et al , 2011; Retelska et al , 2006; Tabaska and Zhang, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Statistical properties of the surrounding sequences were explored in different species, such as yeast (van Helden et al , 2000), fly (Retelska et al , 2006), Arabidopsis and rice (Ji et al , 2010) and human (Chang et al , 2011; Retelska et al , 2006; Tabaska and Zhang, 1999). Although significant progress has been made to the accuracy of poly(A) motif predictors, especially in human DNA sequences, such methods are all based on using sophisticated features that require additional efforts to extract and are highly dependent on domain knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Some research efforts employed machine learning and deep learning approaches to prediction of alternative polyadenylation events and classification of sequences as PASs (Cheng et al 2006;Akhtar et al 2010;Chang et al 2011;Gao et al 2018;Leung et al 2018;Bogard et al 2019). The deep learning approaches highlight the usefulness of convolutional neural networks (CNNs) for regulatory genomics and provide valuable predictions for PAS classification and isoform choice.…”
mentioning
confidence: 99%
“…Another angle to address the prediction problem is through machine learning (ML) approaches, and several such models have been proposed. These include more traditional ML methods like support vector machine and Hidden Markov Model, but also the latest deep learning models, such as DeeReCT-PolyA and DeepGSR (23)(24)(25)(26). Deep learning models generally outperform traditional classifiers because they abandon manually selected features.…”
Section: Current Methods and Limitationsmentioning
confidence: 99%